Cation dynamics by 1H and 13C MAS NMR in hybrid organic–inorganic (CH3CH2NH3)2CuCl4. Issue 59 (4th October 2018) - Lim, Ae Ran; Joo, Yong Lak
Abstract : To understand the dynamics of the cation in layered perovskite-type (CH3 CH2 NH3 )2 CuCl4, the temperature-dependent chemical shifts and spin–lattice relaxation times T 1ρ have been measured using 1 H MAS NMR and 13 C CP/MAS NMR techniques. Abstract : To understand the dynamics of the cation in layered perovskite-type (CH3 CH2 NH3 )2 CuCl4, the temperature-dependent chemical shifts and spin–lattice relaxation times T 1ρ in the rotating frame have been measured using 1 H magic angle spinning nuclear magnetic resonance (MAS NMR) and 13 C cross-polarization (CP)/MAS NMR techniques. Each proton and carbon in the (CH3 CH2 NH3 ) + cation is distinguished in MAS NMR spectra. The Bloembergen–Purcell–Pound (BPP) curves for 1 H T 1ρ in CH3 CH2 and NH3, and for the 13 C T 1ρ in CH3 and CH2 are revealed to have minima at low temperatures. This implies that the curves represent the CH3 and NH3 + rotational motions. The amplitude of the cationic motion is enhanced at the C-end, that is, the N-end of the organic cation is fixed to the inorganic layer through N–H⋯Cl hydrogen bonds, and T 1ρ becomes short with larger-amplitude molecular motions.